Konsep Perlindungan Anak Dalam Perspektif Al Qur’an - Shofiyah Shofiyah (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2017)
From time to time, attention to humanitarian issues has always increased, and even today countries around the world are still faced with grim humanity phenomena, especially against life conditions that threaten the future of children. The successors of this generation have not received maximum attention. Child health conditions are still far below standard, discriminatory in obtaining living facilities, inadequate education, and the treatment of people who are not on the child's interests. Physical violence due to war, to domestic violence and other inhumane acts is still a headline in various media. In the end, all that resulted in children not getting a decent life insurance.